Using podcasts in teaching oral expression to help improve students’ fluency in English an innovative approach that complies with lmd requirement in departments of english in Algeria - Ben-boulaid, Charif (Sciences humaines; Vol. 29 (2013): SCIENCES HUMAINES, 2014)
هذا المقال يهدف إلى تفسير تطبيق التكنولوجيات الجديدة للمعلومات والاتصالات في نظام LMD  في الجزائر لتعليم اللغة الإنجليزية من خلال خيار استخدام "بودكاستس" لتحسين اتقان اللغة . استعمال هذه التكنولوجيا الحديثة يتيح إمكانية دمج شكل جديد من التدريس الذي يجمع بين الترفيه و التعلم مما يساعد على كسب الوقت من أجل معرفة لغوية أفضل.     This article aims at facilitating the implementation of new technologies of information and communication, in the LMD system, in Algeria concerning the successful teaching methods of the English language through the use of Podcasts to improve mastery of language as well as fluency. The combination of the of latest mobile technologies with education offers the possibility of integrating a new form of instruction, known as edutainment, that combines entertainment and learning which can generate outstanding outcomes and considerable gain of time that favors learning in general, and fluency in English in particular.